2022
DOI: 10.1108/jkm-04-2022-0309
|View full text |Cite
|
Sign up to set email alerts
|

Active listening to customers: eco-innovation through value co-creation in the textile industry

Abstract: Purpose This study contributes to current efforts to design and implement sustainable innovation strategies in organisations from the textile industry. This study aims to examine how businesses can overcome the current challenges (e.g. lack of resources) of sustainable innovation by the incorporation of green knowledge of customers into their value co-creation strategies. Such strategies are based on actively listening to customers and addressing their expectations with regard to environmental sustainability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 109 publications
(159 reference statements)
0
12
0
Order By: Relevance
“…The higher the perception of green sincerity toward the focal firm, the higher the consumers' willingness for value co-creation. Furthermore, previous research indicates that individual firms engaging in Green innovation and value cocreation GI can stimulate consumers' positive willingness for value co-creation (Mart ınez-Mart ınez et al, 2023). We extend the research scope from a single firm to the entire supply chain, examine the chain-mediated mechanism of supplier GI and find that the green sincerity perception toward the focal firm positively influences consumers' willingness for value cocreation through the halo effect.…”
Section: Theoretical Implicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…The higher the perception of green sincerity toward the focal firm, the higher the consumers' willingness for value co-creation. Furthermore, previous research indicates that individual firms engaging in Green innovation and value cocreation GI can stimulate consumers' positive willingness for value co-creation (Mart ınez-Mart ınez et al, 2023). We extend the research scope from a single firm to the entire supply chain, examine the chain-mediated mechanism of supplier GI and find that the green sincerity perception toward the focal firm positively influences consumers' willingness for value cocreation through the halo effect.…”
Section: Theoretical Implicationsmentioning
confidence: 85%
“…The green sincerity perception is the conduit through which the “chain liability effects” of the green supply chain are transmitted to consumers of the focal firm and the antecedent for the emergence of the “green halo effect.” The higher the perception of green sincerity toward the focal firm, the higher the consumers' willingness for value co-creation. Furthermore, previous research indicates that individual firms engaging in GI can stimulate consumers' positive willingness for value co-creation (Martínez-Martínez et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…They can replicate what others have found successful, but in an increasingly crowded market, that is not typically a successful direction to take. The work of Martínez-Martínez et al (2022) has shown that small- to medium-sized enterprises (SMEs) in the Spanish textile industry can benefit from active listening to their customers. This is a form communication that is two sided (unlike what someone might consider “normal” listening, which is a passive single-sided activity), whereby both sides prepare and then engage in information transmission, with the receiving side making sure to respond with actions to take forward to demonstrate that they have actively taken in the information the other party wanted to share.…”
Section: Helping the Textile Green Evolutionmentioning
confidence: 99%
“…Trust is a critical factor in digital business ecosystems, as it enables businesses to work together effectively and to share data and information securely. Value co-creation refers to the process of creating value together with customers, suppliers, and other stakeholders, which can help to build trust and foster collaboration in the ecosystem (Martinez-Martinez et al, 2022). Overall, these keywords are interrelated and play important roles in the development and growth of digital business ecosystems, as they enable businesses to collaborate effectively, create new value, and drive progress towards a more sustainable future.…”
Section: Clusters' Compositionmentioning
confidence: 99%